Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.387
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of digitalisation in the context of health care

Abstract: Digitisation of medical records by means of Electronic Patient Record (EPR) systems promises to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Since these activities form significant part of the passport process, the service could not be completely virtualized during and after the lockdown. Given that digitization is a requirement for virtual process and service platformization [35]. Thus, to enable fullly virtual platformization, it is important to consider not only data content but also digitization of physical objects such as stamps and signature and how to use their digital equivalent to avoid the need for physical contact.…”
Section: Discussionmentioning
confidence: 99%
“…Since these activities form significant part of the passport process, the service could not be completely virtualized during and after the lockdown. Given that digitization is a requirement for virtual process and service platformization [35]. Thus, to enable fullly virtual platformization, it is important to consider not only data content but also digitization of physical objects such as stamps and signature and how to use their digital equivalent to avoid the need for physical contact.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving cross-functional collaboration among hospital physicians presupposes the integration of suitable technologies to improve the overall treatment of patients [27,28]. To enhance the overall diagnostic and treatment process further requires IT systems with stored information to be accurate, relevant and integrated as well as quickly accessible when needed [35,36]. However, hospitals still struggle to adopt new technologies in their complex clinical environments and to integrate them into their underlying infrastructure [52].…”
Section: Lesson 3: Antiquated Technical Infrastructure Hinders a Shiftmentioning
confidence: 99%
“…In health care, digital transformation deliberately seeks to answer the question of how the quality of care and its related services can be improved with technology, as both rely on accurate, relevant, integrated and quickly accessible information [35,36]. For example, recent research examined how processes and digital infrastructure must be aligned to drive IT-enabled innovations [37] and whether advanced technologies, such as the Internet of Things (IoT) and artificial intelligence (AI) [38,39], can be integrated to empower caregivers to make evidence-based clinical decisions [28].…”
Section: Introductionmentioning
confidence: 99%
“…Digital transformation is considered one of the most effective responses to face the pressures of stakeholders, improve the quality of health services and reduce costs ( Locatelli et al, 2010 , 2012 ; Secundo et al, 2018 ; Saifudin et al, 2021 ). Furthermore, digital health solutions such as electronic health records, monitoring equipment, tele-health, electronic communications, data analysis, and web and cloud-based tools, if implemented in a targeted manner, have the potential to reduce health inequalities and increase well-being of users through a substantial change in the way in which care and health services are provided to patients ( Or et al, 2014 ; Mihailescu and Mihailescu, 2018 ; Spanò et al, 2021 ; Cerchione et al, 2022 ). In this regard, for example, the digitalisation of health records, understood as the conversion from paper format into computerized form, has consequently improved the overall quality of health care provided, also leading to an increase in the provision of care and patient safety ( Car et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Agarwal et al (2010) found that health care improvements related to digital transformation often fail to materialize. Other authors have instead highlighted problems in the use of electronic health records ( Lorenzi et al, 2008 ; Preko and Boateng, 2020 ) related to delays, safety and costs ( Avison and Young, 2007 ; Mihailescu and Mihailescu, 2018 ). A second problem is instead connected to the different levels of digital maturity of health facilities not only between different European countries but also within individual countries ( Deloitte, 2020 ).…”
Section: Introductionmentioning
confidence: 99%